ASPEK SAINTIFIK DALAM PERENCANAAN PEMBELAJARAN DI SEKOLAH DASAR - Syahidan Nurdin (FITRAH: International Islamic Education Journal, 2021)
The scientific approach is a learning process that is used for developing students' attitudes, skills and knowledge. This study aims to describe the implementation of the scientific approach in teacher lesson plans. The research method is descriptive qualitative by analyzing the teacher's lesson plans. The implementation of the scientific process in the lesson plans shows that all scientific aspects have been found. The results of the analysis of 75 teachers' lesson plans on the development of the scientific learning process found that the implementation was 48.57%.